The Predictive Power of Emotional Intelligence Components on Listening Comprehension Task of Male vs. Female EFL Learners - Niroomand, Seyyedeh Mitra; Rostampour, Mohammad (LANGUAGE ART, 2023)
The present study sought to investigate the feasible association between EFL learners’ emotional intelligence and listening comprehension performance. To attain the goals of the research, a number of English learners were chosen through purposive sampling from some private English institutes in Iran. The participants were asked to answer the Bar-On Emotional Quotient Inventory (EQ-I) and the TOEFL Listening Comprehension Test. The data were analyzed using descriptive and inferential statistics. The Pearson product-moment correlation coefficient was used to examine the relationship between emotional intelligence and listening proficiency and T-test was used to compare male and female participants in listening and emotional intelligence. The results of the study indicated that there was no significant difference between males and females in listening and EQ. Furthermore, significant and meaningful relationships were found between the students’ listening skill and emotional intelligence in total and its components in specific. Furthermore, the results of the multiple regression analyses for the predictability power of emotional intelligence for listening comprehension performance revealed that EI is a proper predictor of learners’ listening task, and among the EQ subscales ‘adaptability’ had the strongest power on EFL learners’ listening comprehension performance. The results of this study can make the teachers, researchers, test developers, material designers aware of how emotional intelligence could influence language proficiency, which proves the potential of the learners. This encourages them to take into a more careful consideration the necessity of using a variety of ways in teaching. Teachers are expected more likely to care about the strength and weakness of learners’ feelings when teaching.